ASSESSMENT OF SMOKING CESSATION INTENTION AMONG MALE ADOLESCENTS AT SMAN 4 KOTA KUPANG BASED ON THE THEORY OF PLANNED BEHAVIOR - Kalake Kebo, Margareta Anggriani; Takaeb, Afrona E. L.; Romeo, Petrus (HEARTY, 2025)
The intention to quit smoking among adolescents plays a crucial role in the success of smoking cessation behavior. According to the Theory of Planned Behavior (TPB), this intention is influenced by three main domains: attitude, subjective norm, and perceived behavioral control. This study aims to describe the intention to quit smoking among male students at SMAN 4 Kota Kupang. A quantitative descriptive design was used, with a total sampling technique involving 46 respondents. The findings showed that 80.4% were classified as light smokers; 39.1% reported a desire to smoke after meals; 67.4% started smoking after the age of 13; 37% smoked in private spaces; and 50% indicated curiosity as the primary reason for smoking. Based on univariate analysis, 63% of respondents had a strong intention to quit smoking; 87% showed a positive attitude toward quitting due to perceived health, economic, and social benefits; 67.4% reported a positive subjective norm supported by family encouragement and social expectations; and 52.2% had strong perceived behavioral control, indicating their ability to refrain from smoking in stressful situations.